Assessing executive functions in free-roaming 2- to 3-year-olds - Schröer, Lisanne; Cooper, Richard P.; Mareschal, Denis (Frontiers in Psychology, 2023)
Introduction Core aspects of executive functions (EFs) are known to be related to academic skills such as literacy and numeracy. However, school outcomes may also be related to higher-level functions such as planning. Nevertheless, few studies have considered assessing natural manifestations of higher-level EFs in children who are on the cusp of entering formal schooling. One reason for this is the difficulty of obtaining ecologically valid measures of EFs in preschool-aged children. Method We describe a novel task - building a striped Duplo tower subject to two constraints - designed to assess planning in real-world multi-action situation. Children were instructed to build a tower to a certain height by alternating between two different colors of blocks. Results Performance on one of the constraints in this task was found to vary with age. Importantly, distinct components of multiple constraints planning performance predicted laboratory-based measures of inhibitory control and working memory efficacy. Discussion Thus, this task provides a simple, cheap and effective way of assessing executive function in toddlers through the observation of natural behavior. It also opens up possibilities to investigate the neurodevelopment of EF in the real world.